Engineering application research on differential protection of distribution network based on 5G communication - CHEN Yongkui; LI Hongmei; ZHU Jihong (Zhejiang dianli, 2023)
There is a difficulty in setting the coordination of over-current protection in the distribution network with distributed power sources and widely laying optical fiber for differential protection in the distribution network， the study on engineering practice of adopting 5G communication in differential protection in the distribution network is tried. Firstly， based on the 5G communication latency measured by the actual device in the URLLC （ultra-reliable and low latency communications） scenario， the form of the latency is analyzed， and the differential protection currentprotection current is chosen according to the current situation that the 5G communication latency occasionally exists the wide range of jitter. On this basis， a technology for constructing communication network based on the topology of distribution network and a construction technology of self-adaption current differential components in the distribution network is proposed. Finally， the current differential protection devices in the distribution network are developed and used in engineering， which proves the feasibility and reliability of the current differential protection in the distribution network based on 5G communication.